A Transcutaneous Carbon Dioxide Monitor Based on Time-Domain Dual Lifetime Referencing - Tufan, Tuna B.; Guler, Ulkuhan (IEEE transactions on biomedical circuits and systems, 2023)
The partial pressure of arterial carbon dioxide plays a critical role in assessing the acid-base and respiratory status of the human body. Typically, this measurement is invasive and can only be taken momentarily when an arterial blood sample is drawn. Transcutaneous monitoring is a noninvasive surrogate method that provides a continuous measure of arterial carbon dioxide. Unfortunately, current technology is limited to bedside instruments mainly used in intensive care units. We developed a first-of-its-kind miniaturized transcutaneous carbon dioxide monitor that utilizes a luminescence sensing film and a time-domain dual lifetime referencing method. Gas cell experiments confirmed the monitor's ability to accurately identify changes in the partial pressure of carbon dioxide within the clinically significant range. Compared to the luminescence intensity-based technique, the time-domain dual lifetime referencing method is less prone to measurement errors caused by changes in excitation strength, reducing the maximum error from \sim 40% to \sim 3% and resulting in more reliable readings. Additionally, we analyzed the sensing film by investigating its behavior under various confounding factors and its susceptibility to measurement drift. Finally, a human subject test demonstrated the effectiveness of the applied method in detecting even slight changes in transcutaneous carbon dioxide, as small as \sim 0.7%, during hyperventilation. The prototype, which consumes 30.1 mW of power, is a wearable wristband with compact dimensions of 37 mm× 32 mm.